First report of maize yellow mosaic virus infecting sugarcane (Saccharum spp.) and itch grass (Rottboellia cochinchinensis) in Nigeria - Yahaya, A.; Al Rwahnih, M.; Dangora, D.B.; Gregg, L.; Alegbejo, M.D.; Kumar, P. Lava; Alabi, O.J. (Scientific Societies, 2017)
During routine surveys conducted from February to July 2015 in the northern guinea savannah region of Nigeria, sugarcane and itch grass (Rottboellia cochinchinensis) plants showing virus-like mosaic symptoms were encountered in farmers’ sugarcane fields in Kaduna State. Symptomatic leaf tissue samples from five randomly selected plants (sugarcane = 4; itch grass = 1) were dried and stored under CaCl2 at room temperature then shipped to Texas A&M AgriLife Research and Extension Center, Weslaco, TX, with USDA-APHIS-PPQ permit (P526P-14-04321) for further analysis. The MagMAX-96 viral RNA isolation kit (Thermo Fisher) was used to isolate total nucleic acid (TNA) from each sample and from a sample subset consisting of pooled leaf tissue materials from both plants. TNA aliquot from the pooled sample was subjected to ribosomal RNA depletion and cDNA library construction using a TruSeq Stranded Total RNA with Ribo-Zero Plant kit (Illumina), then sequenced on the Illumina NextSeq 500 platform. The raw high-throughput sequencing (HTS) reads were analyzed as previously described (Alabi et al. 2015), generating ∼43.5 million Illumina reads (76 nucleotides [nt] in length), of which 31,486 de novo assembled